An assessment of infrastructure readiness for private telecommunication companies in Yemen to implement WiMax network - Al-Sharafi, Ali Mohammed; Othman, Mohamed; Said, Layla Ali Haj (Elsevier, 2012)
With progression in application of communications technology, the scope for deployment of WiMax (wireless interoperability microwave access) network is very promising, particularly in the developing countries. This paper examines infrastructure for private telecommunication companies (Sabafon, MTN, Y, and Yemen mobile) to deploy WiMax network in Yemen, from technical perspectives. This paper provides a glance on telecommunications companies and explores their readiness to deplo? WiMa?. I?fo??atio? was ?olle?ted ?? a ?uestio??ai?e to e?a?i?e ?o?pa?ies i?f?ast?u?tu?e to deplo? WiMa?, a?d to find out the overall readiness to implement it. However, their infrastructure need to develop and need equipment, also the core network needs to be improved. The findings of this paper will be useful to help companies to evaluate their infrastructure and try to introduce a new wireless networks.